2012
DOI: 10.1136/bmjopen-2012-001111
|View full text |Cite
|
Sign up to set email alerts
|

Staff's perception of abuse in healthcare: a Swedish qualitative study

Abstract: ObjectiveThe study aim was to apprehend staff's perception of abuse in healthcare (AHC) after an intervention based on ‘Forum Play’, and make comparisons to preintervention interviews and interviews with male and female patients. AHC can be described as a failing encounter from the patient's perspective.DesignQualitative interview follow-up study.SettingA Swedish Women's Clinic.ParticipantsIn a preintervention study 21 staff members were interviewed. Eligible for the follow-up study were 14 informants who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Additionally, the participants in FP workshops reported having experienced more situations involving moral dilemmas when they acted more according to their own moral beliefs. The picture suggested by the results of study IV, namely, that FP facilitates a shift towards a patient perspective, is supported by Swahnberg and Wijma's study, which was based on interviews with staff from the target clinic before and after a workshop series (120). It showed that FP participants expressed an increased awareness of AHC and a greater willingness to acknowledge AHC and to take on responsibility to act in order to stop AHC.…”
Section: Making Disempowerment Visiblesupporting
confidence: 60%
“…Additionally, the participants in FP workshops reported having experienced more situations involving moral dilemmas when they acted more according to their own moral beliefs. The picture suggested by the results of study IV, namely, that FP facilitates a shift towards a patient perspective, is supported by Swahnberg and Wijma's study, which was based on interviews with staff from the target clinic before and after a workshop series (120). It showed that FP participants expressed an increased awareness of AHC and a greater willingness to acknowledge AHC and to take on responsibility to act in order to stop AHC.…”
Section: Making Disempowerment Visiblesupporting
confidence: 60%
“…Swahnberg and Wijma [46] used an intervention based on "forum play" (see Additional file 4: Table S5) to understand staffs perceptions of Abuse in Health Care (AHC). Findings were particularly relevant to psychological safety as the intervention created an open climate where all staff felt comfortable discussing AHC.…”
Section: Interventions Without Educational Componentmentioning
confidence: 99%
“…One further study [36] found no significant relationship. Three studies [39,46,47] reported improved and one study [48] found mixed results for "communication and collaboration" following interventions. Five studies [38,40,42,44,45] reported positive evaluations by participants postinterventions.…”
Section: Interventions Most Effective At Improving Psychological Safementioning
confidence: 99%
“…Thereafter, ten of the healthcare providers, led by a drama teacher, participated in a one‐day training with forum play (Boal & Jackson, ), focusing on empathetic communication. Forum play has previously been used with good results (Swahnberg & Wijma, ; Zbikowski, Bruggemann, Wijma, Zeiler, & Swahnberg, ). Furthermore, healthcare providers were designated to notify women of their abnormal Pap smear results orally by phone, and schedule an appointment with the physician.…”
Section: Methodsmentioning
confidence: 99%